Turn Taking Patterns of Average Achievers in an Oral Interaction Test (LSP International Journal, 2018)
This study aims to investigate the turn taking patterns of final year undergraduate students who are average achievers in an oral interaction test. The scope of this study focuses on profiling the students’ oral interactive ability in terms of their turn taking patterns in a small group discussion. In order to examine this, the oral test of 14 group discussion tasks in the Universiti Teknologi Malaysia Test of English Communication Skills (UTMTECS) for graduating students were video recorded after consent was sought from the students before the recording took place. The recordings were then transcribed for analysis using an adapted version of Allwright (1988) model of turn taking patterns. From the transcribed files, it is observed that the average achievers mostly gave turns through ‘Neither’ turn giving pattern and gained turns through ‘Take’ turn getting pattern. From the findings, the average achievers in UTMTECS oral test are profiled as moderate speakers of English language. Nevertheless, they are still able to interact with other candidates in the group discussion with functional level of communication skills. This study also provides more insights into the setting of a benchmark to evaluate graduating students’ oral English communication competency and preparedness for the workplace.